Porous electrode
Patent Information
- Application Number
- JP2023572836
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-25
- Filing Date
- 2022-05-23
- Publication Date
- 2025-04-25
AI Technical Summary
Existing porous materials face a trade-off between high surface area, porosity, and mechanical stability, making them unsuitable for applications requiring gas or liquid passage without a support, which compromises their mechanical robustness during cell assembly and processing.
A conductive porous network integrated with a conductive support structure forms a monolithic structure, providing mechanical stability and allowing fluid communication through openings, with a porosity of 50% to 90% and a volumetric surface area of 2 to 90 m²/cm³, enabling self-supporting electrodes.
The integrated structure balances mechanical stability with fluid accessibility, allowing handling during cell assembly and processing, while maintaining high electrochemical surface area and efficient fluid transport.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of porous electrodes, in particular those used in electrolytic cells and other electrochemical devices. [Background technology]
[0002] Highly porous materials with extended surface area and mechanical robustness are attractive for a wide range of applications including catalysis, energy conversion, and storage. Unfortunately, state-of-the-art materials such as metal foams, dealloyed, or Raney metals generally exhibit a trade-off between high surface area, porosity, and mechanical stability. Examples of materials that meet the desired combination of these three properties are described in S. Zankowski et al., ACS Appl. Mater. Interfaces, 10(2018)44634-44644, and S.Zankowski et al., J. Electrochem. Soc., 166 (2019) D227-D235. These materials, called "nanomesh", contain interconnected metal nanowires that are fabricated by electrochemical plating within a three-dimensional aluminum oxide template. Optimization of the fabrication procedure has led to the development of nanomesh with a porosity of 75% and a density of ~30 cm per μm of nanomesh thickness. 2 The result was a rigid nanomesh that combined a high volumetric surface area of 100 nm with a high surface area of 100 nm. The nanomesh described by Zankowski et al. has been shown to be far superior to other state-of-the-art porous nanostructured materials such as nickel foam. For example, nickel nanomesh was compared to nickel foam in electrocatalytic production of H2, and a 4.5 μm nanomesh was shown to outperform a 300-fold thicker (mm thick) nickel foam. This is likely due to the high surface area (130 times versus 10 times) and improved mass transport through the highly porous μm-thick nanomesh electrode.
[0003] Currently, nanomeshes as thin as a few microns cannot be fabricated without a support (either a rigid body such as a silicon wafer or a confined metal foil), which would not be mechanically robust enough to be handled even during cell assembly and processing. However, the presence of a support makes nanomeshes unsuitable as electrodes in many applications that would greatly benefit from complete passage of gases or liquids through the electrode.
[0004] Thus, there remains a need in the art for new highly porous materials that provide increased surface area and mechanical robustness without suffering from the drawbacks mentioned above. Summary of the Invention
[0005] An object of the present invention is to provide a good porous electrode, a method for producing the same, and an electrochemical device including the same.
[0006] The above object can be achieved by the porous electrode, the manufacturing method thereof, and the electrochemical device according to the present invention.
[0007] In a first aspect, the present invention provides a method for producing a composition comprising the steps of: a. a conductive porous network of interconnected wires; and b. conductive support structure; A porous electrode comprising: The network is in direct physical and electrical contact with the supporting structure (e.g., may form a "monolithic" structure), and the network is 2 / cm 3 ~90m 2 / cm 3 and a porosity of 50% to 90%, The surface of the support structure faces away from the network and has openings occupying between 2% and 90% of its surface area, the openings being in fluid communication with the pores of the network.
[0008] In a second aspect, the present invention relates to a method for producing a porous electrode according to any embodiment of the first aspect, comprising the following steps: a. forming a first mold including a network of interconnected channels, the first mold being 2 m 2 / cm 3 ~90m 2 / cm 3 and a porosity of 50% to 90%; and b. forming a second mold on the first mold, the second mold having a surface facing away from the network of interconnected wires and having openings occupying 2%-90%, preferably 50%-70%, of its surface area, the openings suitable for molding a support structure in fluid communication with the pores of the network of interconnected wires; c. filling the first mold with a first conductive material; d. at least partially filling the second mold with a second conductive material; Including, Step b is performed either after step a and before step c, or after step c and before step d; The first conductive material and the second conductive material may be different or the same.
[0009] In a third aspect, the present invention relates to an electrochemical device comprising a porous electrode according to any embodiment of the first aspect, the electrochemical device being selected from an electrolyser (e.g. for water electrolysis, CO2 reduction, N2 reduction, O2 reduction or organic synthesis), a fuel cell, and a battery (e.g. a redox flow battery).
[0010] In a further aspect, the present invention relates to the use of an electrode according to any embodiment of the first aspect as a filter.
[0011] It is an advantage of embodiments of the first aspect that they have good mechanical stability.
[0012] It is an advantage of embodiments of the first aspect that they allow fluid transport into and out of the network.
[0013] It is an advantage of embodiments of the first aspect that the porous electrode has a high electrochemical surface area.
[0014] It is an advantage of embodiments of the second aspect of the invention that the balance between fluid accessibility and mechanical stability can be easily tailored to a particular application.
[0015] Particularly preferred aspects of the invention are set out in the accompanying independent and dependent claims. Features from the dependent claims may be combined with features of the independent claims and with features of other dependent claims as appropriate and not merely as explicitly set out in the claims.
[0016] While there have been constant refinements, changes, and evolutions in devices in this field, the present concepts are believed to represent substantially new and novel improvements which involve departures from prior practice, resulting in more efficient, stable, and reliable devices of this nature.
[0017] The above and other characteristics, nature and advantages of the present invention will become apparent from the following detailed description, taken in conjunction with the accompanying drawings, which illustrate, by way of example, the principles of the invention. This description is given for the purposes of example only, without limiting the scope of the invention. The reference figures quoted below refer to the attached drawings. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic diagram of a porous electrode according to an embodiment of the first aspect of the present invention. [Diagram 2] FIG. 1 is a schematic diagram of a vertical section through an electrolytic cell comprising two porous electrodes according to an embodiment of the first aspect of the present invention. [Diagram 3] FIG. 2 is a diagram showing an example of a production scheme according to an embodiment of the second aspect of the present invention. [Figure 4] Shown diagrammatically are two comparative electrolytic cells (top right and center) and an electrolytic cell according to the invention (top left) with the corresponding current-voltage curves (bottom).
[0019] In the different figures, the same reference signs indicate the same or similar elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described with respect to particular embodiments and with reference to certain drawings but the invention is not limited thereto but only by the claims. The drawings described are schematic and non-limiting. In the drawings, the size of some of the elements may be exaggerated and not drawn to scale for illustrative purposes. The dimensions and relative dimensions do not correspond to actual reductions to the practice of the invention.
[0021] Moreover, terms such as first, second, third, etc. in this specification and claims are used to distinguish between similar elements and are not necessarily used to describe an order, temporally, spatially, sequentially, or otherwise. The terms so used are interchangeable under appropriate circumstances, with the understanding that the embodiments of the invention described herein are capable of operating in orders other than those described or illustrated herein.
[0022] Moreover, terms such as top, bottom, above, below, and the like in this specification and claims are used for descriptive purposes and not necessarily for describing relative positions, and it is to be understood that the terms so used are interchangeable under appropriate circumstances, and that the embodiments of the invention described herein are capable of operation in orientations other than those described or illustrated herein.
[0023] It should be noted that the term "comprising" used in the claims should not be interpreted as being limited to the means recited thereafter, and does not exclude other elements or steps. Thus, this term should be interpreted as specifying the presence of the mentioned and described features, integers, steps or components, but does not exclude the presence or addition of one or more other features, integers, steps or components, or groups thereof. Thus, the term "comprising" includes the case where only the described features are present (and therefore can always be replaced with "consisting of" to limit the scope to the described features), as well as the case where these features and one or more other features are present. Thus, the term "comprising" according to the present invention also includes the absence of additional components as an embodiment. Thus, the scope of the expression "a device comprising means A and B" should not be interpreted as being limited to a device consisting of only components A and B. In the context of the present invention, it means that the components simply related to the device are A and B.
[0024] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the present invention. Thus, the appearances of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification do not necessarily all refer to the same embodiment, although they may. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner, as would be apparent to one of ordinary skill in the art from this disclosure, in one or more embodiments.
[0025] Similarly, in describing exemplary embodiments of the invention, it will be understood that various features of the invention may be grouped together in a single embodiment, figure, or description thereof for the purpose of streamlining the disclosure and aiding in understanding one or more of the various inventive aspects. This method of disclosure, however, is not to be interpreted as reflecting an intention that the claimed invention requires more features than are expressly recited in each claim. Rather, as the following claims reflect, inventive aspects lie in fewer than all features of a single foregoing disclosed embodiment. Thus, the claims following the detailed description are expressly incorporated into this detailed description, with each claim standing on its own as a separate embodiment of this invention.
[0026] Furthermore, some embodiments described herein include some features and not others that are included in other embodiments, but combinations of features of different embodiments are meant to be within the scope of the present invention and form different embodiments, as would be understood by one of ordinary skill in the art. For example, in the following claims, any of the claimed embodiments may be used in any combination.
[0027] Additionally, some of the embodiments are described herein as methods or combinations of method elements that may be implemented by a processor of a computer system or other means for implementing a function. Thus, a processor with the necessary instructions for implementing such a method or method element forms a means for implementing the method or method element. Additionally, the elements described herein of the apparatus embodiments are examples of means for performing the functions performed by the elements for implementing the invention.
[0028] In the description provided herein, numerous specific details are set forth. However, it is understood that embodiments of the present invention may be practiced without these specific details. In other instances, well-known methods, structures and techniques have not been shown in detail in order not to obscure an understanding of this specification.
[0029] The present invention will now be described by detailed descriptions of some embodiments of the present invention. It is obvious that other embodiments of the present invention can be constructed according to the knowledge of those skilled in the art without departing from the technical teachings of the present invention, and the present invention is limited only by the terms of the appended claims.
[0030] In a first aspect, the present invention relates to a porous electrode (1).
[0031] In an embodiment, the porous electrode (1) may be a gas diffusion electrode (1), i.e. an electrode (1) suitable for gas to pass through it from side to side. In the prior art, highly porous materials with extended surface area and mechanical robustness, such as thin metal networks (nanomesh) of a few micrometers, remained supported by a non-porous substrate or were attached to a metal non-porous foil of similar thickness formed by an overplating process. However, for the application of nanomeshes as electrodes in devices using gaseous and / or liquid electrolytes (e.g. electrolyzers producing H2 and O2 from water, electrolyzers producing organic compounds from CO2 reduction, electrolyzers producing ammonia from N2 reduction, or fuel cells with H2 oxidation and O2 reduction), it is advantageous for the electrodes to be open on opposite sides. In the case of gapless (also called zero gap) electrolyzers, i.e. when the electrodes are in contact with a separator or membrane, it is necessary to open the electrodes on opposite sides. With the current state of the art, nanomeshes as thin as a few micrometers cannot be made without a support, which does not have the mechanical robustness to handle during cell assembly and processing. The porous electrode (1) of the present invention is suitable for use in devices with gas / liquid passing through the electrode by comprising a support structure (3) having openings (5) while displaying portions (network (2)) with high porosity and extended surface area, and overall mechanical robustness for handling both during cell assembly and processing.
[0032] The porous electrode (1) comprises a conductive porous network of interconnected wires (2) and a conductive supporting structure (3).
[0033] Both the conductive porous network (2) and the conductive support structure (3) are porous.
[0034] The presence of the conductive support structure (3) allows the porous electrode (1) to be free-standing and capable of being handled without losing mechanical integrity.
[0035] The network (2) is in direct physical and electrical contact with the support structure (3). In a preferred embodiment, this is achieved by forming the network (2) and the support structure (3) integrally. In other words, the network (2) and the support structure (3) may be monolithically integrated. In these embodiments, the network (2) and the support structure (3) typically do not comprise the same material. In other embodiments, the network (2) and the support structure (3) do not comprise the same material. Different materials for the network (2) and the support structure are advantageous for independently tuning the mechanical and catalytic properties.
[0036] Preferably, both the conductive network (2) and the conductive support structure (3) comprise the same material, most preferably nickel, a nickel alloy, or copper, but their material compositions may also be different, e.g., a copper conductive network (2) and a nickel conductive support structure (3).
[0037] The volume and surface area of network (2) is 2 m 2 / cm 3 ~90m 2 / cm 3 It is.
[0038] The porosity of the network (2) is 50% to 90%.
[0039] In an embodiment, the conductive network of interconnected wires (2) may comprise a metal.
[0040] In embodiments, the conductive network of interconnected wires (2) may comprise Ni, a Ni alloy, or Copper. Preferably, the conductive network of interconnected wires (2) comprises Ni.
[0041] Preferably, the wire is metallic or has a metallic core and a coating thereon.
[0042] More preferably, the wire is formed from Ni (or a Ni alloy or Cu) or has a Ni (or a Ni alloy or Cu core) with a coating thereon.
[0043] Most preferably, the wire is formed from Ni or has a Ni core with a coating thereon.
[0044] In an embodiment, the conductive network of interconnected wires (2) may have a total thickness of 1 to 100 μm, preferably 2 to 10 μm.
[0045] In embodiments, the conductive network of interconnected wires (2) may have a total thickness of 1-100 μm and the surface of the support structure facing away from the network may have openings (5) occupying 51-90% of its surface area, which is advantageous as it provides the network with sufficient strength to withstand the relatively high fluid flows permitted by the openings in the support structure.
[0046] In the embodiment, the wire has a thickness of 10 to 200 nm, preferably 30 to 60 nm.
[0047] The surface of the conductive support structure (3) facing away from the network (2) has openings (5) occupying 2-90%, preferably 15-75%, more preferably 50-70% of its surface area. The openings (5) are in fluid communication with the pores of the network (2). In other words, these openings allow the transport of fluids (liquids and / or gases) in and out of the network (2). Figure 1 is a schematic diagram of a porous electrode (1) according to a first embodiment, comprising a conductive porous network (2) (black) and a conductive support structure (3) (white) thereon. Fluids (liquids or gases) crossing the network (2) via the support structure (3) are represented by upper arrows. Fluids (liquids or gases) crossing the support structure (3) via the network (2) are represented by lower arrows.
[0048] The support structure (3) acts as a mechanical reinforcement for the network (2).
[0049] In an embodiment, the conductive support (3) may comprise a metal.
[0050] In an embodiment, the conductive support structure (3) may comprise Ni, a Ni alloy, or Cu, preferably Ni.
[0051] The conductive support structure (3) may be in any form, typically forming a pattern.
[0052] In an embodiment, the conductive support structure (3) may form a grid, such as a honeycomb grid, which is advantageous as it allows for high mechanical strength to be obtained.
[0053] In an embodiment, the conductive support structure (3) may form a collection of parallel lines, which is advantageous as it allows for particularly good flow.
[0054] In an embodiment, the pattern of support structures (3) may be formed with ridges having a width measured perpendicular to the height of the ridges of 50 to 1000 μm. For example, the ridges may cross-connect to form a grid, such as a honeycomb grid, and the width of the ridges that interconnect to form the grid may be 50 to 1000 μm. As another example, where support structures (3) form a series of parallel lines, the width of these lines may be 50 to 1000 μm.
[0055] In an embodiment, the conductive support structure (3) can have a total thickness (or height) of 1 to 100 μm, preferably 2 to 20 μm, more preferably 2 μm to 10 μm, and even more preferably 3 μm to 7 μm.
[0056] In embodiments, the porous electrode may be a gas diffusion electrode for CO2, N2 or O2 reduction from the gas phase, for fuel cells, or for organic synthesis.
[0057] Any feature of the first aspect may be correspondingly described in any embodiment of the other aspect.
[0058] In a second aspect, the present invention relates to a method for forming a porous electrode (1) according to any embodiment of the first aspect, the method comprising steps a, b, c and d. In comparison to prior art processes, the method of the present invention allows for the formation of a porous electrode (1) having sufficient porosity to allow a fluid (e.g. gas) to pass therethrough, while the support structure (3), e.g. a grid support structure (3), has sufficient density to act as a "window frame" for the typically μm-thin network (2), thereby providing mechanical support without impeding the passage of the fluid.
[0059] Step a comprises forming a first mould containing a network of interconnected channels (2), the mould being suitable for forming a conductive network (2) as described in any embodiment of the first aspect. For example, the mould may be 2m 2 / cm 3~90m 2 / cm 3 The material may be suitable for forming a conductive network of interconnected wires (2) having a volumetric surface area of 0.1 mm or less, and a porosity of 50% to 90%.
[0060] In an embodiment, step a may include anodizing the metal layer.
[0061] In an embodiment, step a may include anodizing the layer of an alloy of Al and Cu.
[0062] Preferably, the alloy of Al and Cu is 98.0 to 99.9 at% aluminum, and 0.1 to 2.0 at% copper, may also include.
[0063] More preferably, the alloy of Al and Cu is 99.0 to 99.9 at% aluminum, and 0.1 to 1.0 at% copper, may also include.
[0064] Most preferably, the alloy of Al and Cu is 99.5 to 99.9 at% aluminum, and 0.1 to 0.5 at% copper, may also include.
[0065] These at % can be measured, for example, by Rutherford backscattering spectroscopy (RBS).
[0066] In an embodiment, the alloy layer may be supported on a substrate. In an embodiment, the substrate may include a Si substrate having a TiN layer thereon, and the alloy layer may be on the TiN layer. In an embodiment, anodizing the Al / Cu alloy layer may include subjecting the Al / Cu alloy layer to a voltage of 10 to 250 V, preferably 30 to 85 V. This is preferably performed in an acid solution.
[0067] An example of a suitable acid solution is an oxalic acid solution. Other suitable acid solutions are sulfuric acid solution and phosphoric acid solution. The concentration of the acid solution can be, for example, 0.1 to 0.5 M, preferably 0.2 to 0.4 M. The temperature of the acid solution can be, for example, -5 to 50°C, preferably 20 to 40°C.
[0068] The voltage is preferably maintained until a mold is obtained, for example, 5 minutes after the current begins to drop.
[0069] Various Al / Cu alloys exhibit similar behavior by forming similar interchannel distances at similar voltages. Small interchannel distances in the range of 20-50 nm can typically be obtained under voltages of 10 to about 20 V (e.g., by using H2SO4 as the electrolyte). Interchannel distances of about 51-125 nm can typically be achieved under voltages of 21 to about 60 V (e.g., in H2C2O4). Larger interchannel distances of 126-225 nm can typically be achieved at voltages of 61-90 V (e.g., in H3PO4). It is noted that even higher interchannel distances can be obtained at even higher voltages.
[0070] The average interchannel distance between any two adjacent channels can be tuned from about 20 nm to about 225 nm, for example, by increasing the voltage from 10 V to 90 V (and eventually adapting the acid accordingly), with the interchannel distance being set by the applied cell voltage. The interchannel distance increases with voltage and is generally independent of the purity of the aluminum or the nature of the impurities.
[0071] If a TiN layer is present, the anodization step transforms the TiN layer into a TiO2 layer. After the anodization step, a step of removing the TiO2 layer may be performed. This can be done, for example, by using a suitable liquid etchant. An example is a solution containing NH4OH, H2O2 and H2O. A time period of 1 to 5 minutes (for example, 3 to 4 minutes) is usually sufficient to remove the TiO2 layer. Preferably, a cleaning step is performed between steps a and b. In an embodiment, this cleaning step may comprise rinsing the structure obtained from step a with demineralized water.
[0072] Step b comprises forming a second mould on the first mould, the second mould being suitable for moulding a conductive support structure (3) according to any embodiment of the first aspect. For example, the second mould may be suitable for moulding a support structure (3) having a surface facing away from the network of interconnected wires (2) and having openings (5) occupying 2-90% of its surface area, the openings (5) being in fluid communication with pores of the network of interconnected wires (2).
[0073] Preferably, the second mould comprises wax. Preferably, forming the second mould may comprise printing the second mould on the first mould. Preferably, the second mould is applied by inkjet printing. More preferably, the second mould comprises wax and is applied by inkjet printing. In an embodiment, the pixel size of the inkjet printing may be 30-60 μm, preferably 40-50 μm. In an embodiment, the second mould may comprise a plurality of pillars or ridges. Preferably, the pillars are arranged in a regular pattern. Preferably, the average height of the pillars or ridges (i.e. the distance between the top and bottom surfaces of the pillars or ridges measured perpendicular to the top surface of the pillars or ridges) is 5 μm-200 μm, preferably 10 μm-50 μm. Preferably, the relative standard deviation of the height of the pillars or ridges is 10% or less, more preferably 5% or less. Preferably, the average width of the pillars or ridges, i.e., their smallest dimension measured along and parallel to the top surface of the pillars or ridges, is between 30 and 1000 μm, preferably between 100 and 500 μm, more preferably between 200 and 300 μm. Preferably, the relative standard deviation of the pillar or ridge width is less than 10%, more preferably less than 5%. Preferably, the average pillar or ridge width measured at the top of the pillar or ridge is within 10%, more preferably within 5% of the average pillar or ridge width measured at the base of the pillar or ridge. The horizontal cross section of the pillars may be of any shape. Preferably, the horizontal cross section of the pillars is hexagonal. This allows the formation of a conductive structure having a honeycomb shape, which provides good mechanical support while ensuring a large proportion of the openings (5) in the support structure (3). The pattern comprises 2-90% open area, preferably 15-90% open area, more preferably 50-90% open area, and even more preferably 65-90% open area.
[0074] Step b is carried out using wax at a temperature of preferably 50 to 200°C, preferably 90 to 185°C, more preferably 90 to 140°C, and even more preferably 90 to 120°C.
[0075] During step b, the first mould is preferably kept at a temperature below 50°C.
[0076] For example, the temperature can be kept at room temperature (for example at a temperature between 15 and 30° C. or between 20 and 25° C.). Room temperature is advantageous if step b is carried out after step c. In fact, since the first mould is already filled, there is no risk of contaminating the first mould with undesirable material by forming the second mould. The solidification of the wax by contact with the first mould can be carried out at room temperature, which is advantageously easy and cheap to maintain.
[0077] In an embodiment, the first mould may be kept at a temperature of 15° C. or below. For example, it may be kept at 5° C. or below or 0° C. or below. Indeed, when the second mould is applied, the first mould is not yet filled, so that it is advantageous for the material forming the second mould to solidify in contact with the first mould. This reduces the risk of contamination of the first mould with undesired material.
[0078] Step c includes filling the first mold with a first conductive material. In an embodiment, step c can include two sub-steps, step c1 and step c2. In step c1, a copper layer is formed on the bottom of the first mold (typically on the substrate on which the first mold is present, e.g., on the TiN layer in the case of a Si substrate having a TiN layer thereon). The thickness of the copper layer is, for example, 10 to 1000 nm, preferably 30 to 100 nm, more preferably 50 to 80 nm. Step c1 typically includes forming a copper layer on the bottom surface of the first mold by electrodeposition of copper. Any copper plating bath is suitable for carrying out step c1. In an embodiment, step c1 includes forming a copper layer on the bottom surface of the first mold by electrodeposition of copper under acidic conditions. 2+ For example, the solution may include sodium citrate or sulfuric acid. 2+The concentration of may be 0.001-1.0 mol / l. For example, a solution containing 0.5 mol / l CuSO4x5H2O and 1 mol / l sodium citrate is suitable. In embodiments where sulfuric acid is present in the solution, the concentration of sulfuric acid is preferably kept low to avoid etching of the alumina, and may be, for example, 10 mmol / l-30 mmol / l, preferably 15 mmol / l-25 mmol / l.
[0079] Cu 2+ The solution is contacted with the first mold and −2 mA / cm 2 ~-40mA / cm 2 (galvanostatic deposition), preferably -5mA / cm 2 ~-15mA / cm 2 or a potential of -0.2 to -0.8 V, preferably -0.3 to -0.7 V (potential electrostatic deposition). In an embodiment, the electrodeposition time is 10 seconds to 20 minutes. The temperature of the solution used in step c1 may be, for example, 15°C to 40°C, for example, 25°C to 35°C.
[0080] In an embodiment, step c2 comprises filling the remaining portion of the first mould by electrolytic deposition of Ni. For this purpose, a solution comprising Ni sulphamate, boric acid and NiCl2 can be used. The concentration in Ni sulphamate may be, for example, 0.80-1.00 mol / l. The concentration of boric acid may be, for example, 0.40-0.60 mol / l. The concentration in NiCl2 may be, for example, 0.03-0.05 mol / l. One or more additives may be added to the solution. For example, a wetting agent or an electroplating enhancer may be added. Step c2 is typically carried out at -2 mA / cm 2 ~-10mA / cm 2 , preferably -3mA / cm 2 ~-7mA / cm 2A current density of 100 μm is applied. Step c2 is typically performed until the first mould is completely filled, which usually takes 20 min to 50 min. If step c is performed before step b, it is advantageous not to overfill the mould (during step c2). In this way, no Ni overlayer is formed on and above the first mould. In an embodiment, the filled mould, and thus the formed support structure (3), may have a height of 1 to 100 μm, preferably 2 to 20 μm, more preferably 2 μm to 10 μm, and even more preferably 3 μm to 7 μm.
[0081] Step d comprises at least partially filling the second mould with the second conductive material. Since moulds tend to have more regular edges at their bottom and middle, then at the top, it is advantageous to only partially fill the mould during step d. For example, step d can fill 10-90%, preferably 15-75% of the height of the second mould. The first and second conductive materials can be different or the same. Preferably, step d comprises filling the second mould by electrodeposition of Ni. For example, the solution used can be the same as in step c2. For this purpose, a solution containing Ni sulphamate, boric acid and NiCl2 can be used. The concentration of Ni sulphamate is, for example, 0.80-1.00 mol / l. The concentration of boric acid is, for example, 0.40-0.60 mol / l. The concentration of NiCl2 is, for example, 0.03-0.05 mol / l. One or more additives may be added to the solution, for example a wetting agent or an electroplating enhancer. The solution is preferably left in contact with the second mask for 2 to 8 minutes, more preferably 3 to 7 minutes, before the current is applied. This time allows for etching of the top oxide of the first mold.
[0082] Step b is performed after step a, before step c, or after step c and before step d.
[0083] The second mold is formed on top of the first mold, so that the support structure (3) is built directly onto the network (2) structure, allowing the support structure (3) to be seamlessly connected to the network (2) to form a monolithic structure.
[0084] In an embodiment, steps c and d may be carried out by plating.
[0085] In an embodiment, the method may further comprise removing the first and second molds from the conductive porous network (2) and the conductive support structure (3), respectively. Preferably, the second mold can be removed before removing the first mold. This is advantageous since it avoids removing part of the network (2) together with the second mold. Also, preferably, the second mold can be removed before peeling off the conductive network (2) from the substrate (e.g., a Si substrate).
[0086] In an embodiment, removing the second mold may include exposing the second mold to a suitable solvent that dissolves the second mold, particularly with respect to the first mold, network (2), and support structure (3) (e.g., acetone for an anodized Al / Cu alloy first mold, wax second mold, Ni support structure (3), and Ni network (2)). Once the second mold is removed, the remaining structure can be washed with deionized water.
[0087] In an embodiment, at least a part of the first mould (e.g. the part formed in step c2) may be selectively removed with respect to the support structure (3) and the network (2). For this purpose, in the case of a Ni support structure (3) and a Ni network (2), a solution capable of dissolving the first mould selectively with respect to Ni may be used. If the first mould is made of an anodized Al / Cu alloy, this solution may be an alkaline hydroxide solution. Preferably, it is a hydroxide solution with a concentration of 0.5 mol / l to 2 mol / l. More preferably, it is a concentration of 0.8 mol / l to 1.2 mol / l. A preferred hydroxide is KOH. The exposure of the first mould to the solution may be, for example, from 20 min to 180 min, preferably from 40 min to 120 min, more preferably from 50 min to 90 min.
[0088] In an embodiment, if step c1 involves the formation of a copper layer on the bottom of the first mold, this layer can finally be removed using a solution containing an organic acid (e.g., acetic acid), H2O2, and water, or a solution of ammonium or potassium persulfate. Usually, 1 to 20 minutes is sufficient. Finally, the resulting porous electrode (1) can be washed by immersion in deionized water. In an embodiment, it can then be dried at a temperature of 30 to 100 °C.
[0089] FIG. 3 shows an example of a fabrication scheme according to an embodiment of the present invention. First, an assembly is provided, including a Si substrate, a TiN layer on the Si substrate, and an Al / Cu alloy layer on the TiN layer. A first mold (6) is formed by exposing the Al / Cu alloy (0.4-0.5 wt.% Cu doped Al) layer to a 0.3 M oxalic acid solution at 30° C. under mechanical stirring at 1800 rpm and applying a voltage of 40 V through the solution. This voltage is maintained until 200 seconds after the current starts to drop, resulting in over anodization of the alloy layer. This process (AAO template formation) results in the formation of a first mold (6) containing a network of interconnected channels (2), the first mold (6) being suitable for forming a conductive network (2) as described in any embodiment of the first aspect. At the bottom of the first mold (6), the TiN layer has been transformed into a TiO2 layer. The TiO2 layer was then removed by exposure for 3.5 min to a solution containing NH4OH, H2O2, and H2O. The resulting structure was washed five times with demineralized water before proceeding to the next step.
[0090] At this stage, step c was carried out. First, a Cu layer was formed on the bottom of the first mould (6). For this purpose, a solution containing 0.5 mol / l CuSO4x5H2O and 1 mol / l sodium citrate at 30°C was used. This solution was charged with -10 mA / cm 2 was applied for 50 seconds to form a 500 nm Cu layer on the bottom of the first mould (6). An alternative version of this Cu layer formation process can be carried out by using a more dilute Cu solution. For example, a solution containing 5 mM CuSO4 and 20 mM H2SO4 at an applied potential of -0.6 V can be used, which will form a more homogeneous 70 nm thick Cu layer when transferring a total charge of -6.4 C. Secondly, a Ni layer was formed on the Cu layer, thereby filling the remaining part of the network of interconnecting channels (2). For this purpose, a solution containing 0.91 mol / l Ni sulfamic acid, 0.49 M boric acid, 0.04 mol / l NiCl2x6H2O, 2.5 ml / l additive NikalPC-8 and 2 ml / l wetting agent was prepared at 40 °C, with a current of -5 mA / cm 2A current of 1000 s was applied until the network of interconnecting channels (2) was completely filled. Care was taken not to overfill the channels, thus avoiding the formation of a Ni overlayer on and above the network of interconnecting channels (2). This step took 30-40 min with the freshly prepared solution.
[0091] Step b is then performed by forming a second mould (7) on top of the first mould (6) (and thus on top of the conductive network (2)), the second mould (7) being suitable for moulding the conductive support structure (3) as described in any embodiment of the first aspect. In this example, the second mould (7) was formed from wax and inkjet printed onto the first mould (6). Because the first mould (6) was pre-filled with the conductive network (2), the printing of the second mould (7) could be performed on a relatively flat surface, with little or no penetration of the wax into the first mould (6). The length of the second mould (7) was 55 mm. The pixel size of the inkjet printing was 31.25 μm. The pattern of the second mould (7) was a collection of hexagons with a length of 250 μm and a pitch of 345 μm. The pattern comprises an open area of 85.5%. To apply the wax to the Ni-filled first mold (6), the wax was first heated to 110° C., while the Ni-filled first mold (6) was kept at room temperature. The printing time was less than 60 seconds.
[0092] Step d was then carried out by exposing the second mould (7) to a solution at 40° C., containing 0.91 mol / l Ni sulphamic acid, 0.49 mol / l boric acid, 0.04 mol / l NiCl2*6H2O, 2.5 ml / l Nickel PC-8 and 2 ml / l Wetting agent NW. This solution was left in contact with the second mould (7) for 5 minutes, after which a first current was passed through it. This 5 minutes allows etching of the oxide on top of the first mould (6). A current of −10 mA / cm was then applied to the area of the conductive network (2) (using the open area of the first mould). 2 A current of -5 mA / cm was applied for 500 seconds, followed by -5 mA / cm in the open areas of the wax mask. 2A current of 1000 .ANG. was applied for 3200 seconds. As a result, the Ni support structure (3) became 5 μm.
[0093] The second mold (7) was then removed before removing the first mold (6) and before peeling off the conductive network (2) from the Si substrate. This was done to avoid removing part of the Ni network (2) along with the second mold (7). For this purpose, the structure obtained in step d was exposed to fresh acetone at room temperature for 5 minutes, rinsed with water and then again exposed to fresh acetone for 5 minutes. The structure obtained was then rinsed 10 times with deionized water.
[0094] To remove the first mold (6), it was placed in contact with a 1 M aqueous KOH solution for 60 minutes. At this point, the monolithic structure may already peel off from the support wafer, but in most cases this will occur during the subsequent etching step.
[0095] The bottom Cu layer, which appears as a red glowing layer, was then etched away by immersing the conductive network (2) for 3 min in a Cu etching solution containing acetic acid, HO, and HO. The resulting porous electrode (1) was peeled off from the support wafer, washed by immersion in deionized water, and then dried at 80 °C.
[0096] In a third aspect, the present invention relates to an electrochemical device. The electrochemical device comprises a porous electrode (1) according to any embodiment of the first aspect. The electrochemical device is selected from electrolyzers, fuel cells, and batteries (e.g., redox flow batteries). Examples of electrolyzers include those that produce H2 and O2 from water, those that produce organic compounds from CO2 reduction, those that produce ammonia from N2 reduction, and those that produce water from O2 reduction.
[0097] The electrolytic cell of the invention may comprise two porous electrodes (1) according to the invention, each electrode (1) contacting a different side of a membrane (4). In an embodiment, the electrolytic cell may comprise an anode and a cathode, both according to an embodiment of the first aspect. In an embodiment, the membrane (4) may be an anion or cation exchange membrane (4).
[0098] Figure 2 shows an electrolytic cell comprising two porous electrodes (1) according to the first embodiment of the invention. More specifically, an alkaline electrolytic cell is depicted comprising two porous electrodes (1) according to the first embodiment separated by a membrane (4). The networks (2) of both electrodes face each other, while the supports (3) of both electrodes (1) are spaced apart from each other. The porous electrode (1) depicted on the left side of the electrolytic cell acts as a cathode, where water is reduced to H2 and 2OH. - The electrolyte inlet is drawn at the bottom left of the electrolytic cell. OH produced at the cathode - The current passes through the membrane (4) and reaches the anode, which contains a porous electrode (1), depicted on the right side of the electrolytic cell. At the top left of the electrolytic cell is an outlet, where hydrogen gas evolved at the cathode can be collected from the electrolytic cell. At the bottom right is an inlet, where the electrolyte enters. At the top right is an outlet, where oxygen gas evolved at the anode by oxidation of the hydroxyl anions can be collected from the device.
[0099] Taking the application of a metal network (2) in the membrane (4)-porous electrode (1) assembly of this water electrolyzer as an example, it is highly advantageous for the network (2) to be able to penetrate the electrolyte. This allows catalytic reactions leading to ion exchange between the cathode electrode (1) and the anode electrode (1) through the separation membrane (4). Furthermore, gaseous products (H2 and O2) formed inside the network (2) should usually be removed from the nanostructure through the open front side. Furthermore, the network (2) must usually withstand the mechanical stresses caused by the cell assembly, high solution flow rates, gas bubble formation, and finally the pressure exerted on the electrolyzer. This is ensured by the conductive support structure (3).
[0100] The catalytic efficiency of electrolysers, such as that shown diagrammatically in Figure 2, benefits greatly from the large number of exposed active sites provided by the high surface area network (2) of the porous electrode (1) according to the first embodiment. This allows for the production of low-cost green hydrogen, which can be used as a form of energy storage, for the chemical industry, or to generate electricity in fuel cells. Similarly, fuel cells benefit from the large number of exposed active sites of the network (2) of the porous electrode (1).
[0101] The following experiments were carried out to evaluate the performance of the electrolytic cell according to the third embodiment using the porous electrode (1) according to the first embodiment of the present invention. For this purpose, a one-cell renewable PEM electrolytic cell kit from H-TEC Education was applied and fitted with the electrode (1) according to the first embodiment of the present invention or a reference electrode. The electrolytic cell kit includes a proton exchange membrane and two electrodes. In all configurations, the proton exchange membrane was replaced by an anion exchange membrane (4) Fumasep FAB PK-130 and the electrode was replaced by one of the following: a 1.6 mm thick Ni foam Ni-5763 electrode from Recemat BV (first comparative configuration, triangles in FIG. 4), a 5 μm thick Ni foam Ni-5763 electrode from Recemat BV (second comparative configuration, disks in FIG. 4), and a 1.6 mm thick Ni foam Ni-5763 electrode from Recemat BV in physical contact with a porous electrode (1) according to the invention, whose conductive porous network (2) is in physical contact with the membrane (4). Although not necessary, the Ni foam helps to ensure good contact between the contact plate and the membrane (4). In an embodiment, a metal foam (e.g., Ni metal foam) can be present on the support structure (3) of the electrode (1) according to the invention. For example, a metal foam can be present between the electrode (1) and the contact plate of the electrolytic cell. The porous electrode (1) according to the invention comprises a 4 μm thick Ni porous network (2) of interconnected wires and a 5 μm thick Ni support structure (3). The presence of the Ni support structure (3) made the porous electrode (1) easy to handle. The Ni foam Ni-5763 electrode from Recemat BV has a porosity of 96%. The 5 μm thick support structure (3) had openings (5) occupying 15% of the top and bottom surface areas. Before use, the anion exchange membrane (4) was first soaked in 1 M KOH for 24 hours. The device was used to generate hydrogen and oxygen from deionized water with the aid of a power supply. In each configuration, the electrolyte was at 20.3° C., the flow rate was 5 ml / min, and the electrode area was 16 cm. 2Each potential was applied for 5 minutes with the anode as the working electrode and the cathode as the counter electrode. Impedance measurements were taken after 3 minutes for each potential step to determine the ohmic resistance for iR correction. Figure 4 shows a schematic of the three configurations (top) and the corresponding current-voltage curves (bottom). As can be easily seen from these curves, the configuration according to the present invention allows for a higher current density at a much lower overpotential than the comparative configuration.
[0102] The gas diffusion electrode as an electrochemical device of the present invention may be an electrocatalytic system for the reduction of CO2, N2 or O2 from the gas phase.
[0103] An example of a battery according to the third embodiment is a redox flow battery. The use of a porous electrode (1) according to the first embodiment allows the flow of electrolyte between the anode and the cathode.
[0104] In an embodiment, a battery according to the invention may comprise an anode and a cathode both according to any embodiment of the first aspect of the invention, for example the battery may be a redox flow battery comprising both an anode and a cathode.
[0105] A typical fuel cell according to the present invention involves H2 oxidation and O2 reduction.
[0106] In an embodiment, the fuel cell may comprise an anode and a cathode, both according to any embodiment of the first aspect of the invention.
[0107] In a further aspect, the present invention relates to the use of an electrode according to any embodiment of the first aspect as a filter, in an embodiment of this use, the surface of the support structure facing away from the network has openings (5) representing between 2 and 50%.
[0108] Although preferred embodiments, specific structures and configurations, as well as materials, of the devices according to the invention have been discussed herein, it should be understood that various changes or modifications in form and details can be made without departing from the scope and spirit of the invention. For example, any formulas given above are merely representative of procedures that may be used. Functions may be added or deleted from the block diagrams, and operations may be interchanged between functional blocks. Also, steps may be added or deleted to the methods described within the scope of the invention.
Claims
1. A porous electrode (1), a. a conductive porous network of interconnected wires (2); and b. A conductive support structure (3), The network (2) is in direct physical and electrical contact with the support structure (3), and the network (2) is 2 m 2 / cm 3 ~90m 2 / cm 3 and a porosity of 50% to 90%, The surface of the support structure (3) faces away from the network (2) and has openings (5) occupying 2% to 90% of its surface area, the openings (5) being in fluid communication with the pores of the network (2).
2. 2. The electrode (1) of claim 1, wherein the conductive network (2) of interconnected wires comprises Ni.
3. 3. The electrode (1) according to claim 1 or 2, wherein the conductive porous network (2) of interconnected wires has a total thickness of 1 to 100 μm, preferably 4 to 10 μm.
4. 3. The electrode (1) according to claim 1 or 2, wherein the conductive support structure (3) comprises Ni or Cu.
5. Electrode (1) according to claim 1 or 2, wherein the wire is 10 to 200 nm thick, preferably 30 to 60 nm thick.
6. 3. The electrode (1) according to claim 1 or 2, which is a gas diffusion electrode (1).
7. A method for forming a porous electrode (1) according to claim 1 or 2, comprising the steps of: a. forming a first mold (6) containing a network of interconnected channels (2), the first mold (6) being 2 m 2 / cm 3 ~90m 2 / cm 3 forming a first mould (6) suitable for forming a network of interconnected wires (2) having a volumetric surface area of 0.01 mm and a porosity of 50% to 90%; b. forming a second mold (7) on the first mold (6), the second mold (7) having a surface facing away from the network of interconnected wires (2) and having openings (5) occupying 2-90% of its surface area, the openings (5) being suitable for molding a support structure (3) in fluid communication with the pores of the network of interconnected wires (2); c. filling the first mold (6) with a first conductive material; d. at least partially filling the second mould (7) with a second conductive material; Step b is performed either after step a and before step c, or after step c and before step d; A method for forming a porous electrode (1), wherein the first conductive material and the second conductive material are different or the same.
8. The method of claim 7, wherein the step of forming the first mould (6) comprises the step of anodising a metal layer.
9. The method according to claim 7, wherein the step of forming the second mould (7) comprises printing the second mould (7) on the first mould (6).
10. The method of claim 9, wherein the printing is inkjet printing.
11. 8. The method according to claim 7, wherein the second mould (7) is formed from wax.
12. Electrochemical device comprising a porous electrode (1) according to claim 1 or 2, the electrochemical device being selected from electrolysers, fuel cells and batteries.
13. 13. An electrolytic cell according to claim 12, comprising an anode and a cathode according to claim 1 or 2.
14. 13. A fuel cell according to claim 12, comprising an anode and a cathode according to claim 1 or 2.
15. 13. The battery of claim 12, which is a redox flow battery comprising the anode and cathode of claim 1 or 2.